2017
DOI: 10.1590/1413-70542017416000517
|View full text |Cite
|
Sign up to set email alerts
|

Selenium behavior in the soil environment and its implication for human health

Abstract: Selenium (Se) is an important element that was discovered in 1817, and since the 1960s, it has been regarded as an essential micronutrient for both animals and humans, playing among other functions a relevant role in the antioxidant system of mammals. Inadequate blood Se levels in the human body is a well-known concern in many parts of the world. This malnutrition problem is often due to Se-poor diet, probably as a result of the low Se availability in soils where crops are growing. Nowadays, it is known that n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 75 publications
(44 citation statements)
references
References 80 publications
1
41
0
2
Order By: Relevance
“…This difference may be attributed to the fact that the Se(VI) is bound mainly by outer-sphere complex, while the Se(IV) mainly forms inner-sphere complex, being this last Se specie less available and less mobile. Lopes et al (2017) reported that differences in adsorption behavior of Se(VI) and Se(IV) reflect in different amounts of Se to be uptaken up by plant roots. So, taking into account that the Se(VI) is more available in tropical soils, studies involving agronomic biofortification of agricultural crops with Se through application of Se should give priority for this Se specie.…”
Section: Se(iv) Desorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…This difference may be attributed to the fact that the Se(VI) is bound mainly by outer-sphere complex, while the Se(IV) mainly forms inner-sphere complex, being this last Se specie less available and less mobile. Lopes et al (2017) reported that differences in adsorption behavior of Se(VI) and Se(IV) reflect in different amounts of Se to be uptaken up by plant roots. So, taking into account that the Se(VI) is more available in tropical soils, studies involving agronomic biofortification of agricultural crops with Se through application of Se should give priority for this Se specie.…”
Section: Se(iv) Desorptionmentioning
confidence: 99%
“…The concern about Se around the world has been justified due to the low Se contents found in soils in different regions worldwide (Lopes et al 2017). In Brazil, studies showed that the soils and consequently the agricultural crops and foods are poor in Se (Carvalho et al 2019;Gabos et al 2014a;Matos et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…It exists mainly as elemental mercury, the bivalent form of Hg 2+ , and as the organic methylmercury (MeHg) in most natural environments (Arcagni et al, 2018;Coulibaly, Bamba, Yao, Zoro, & Rhazi, 2016;Harris, Pickering, & George, 2003). Selenium (Se), however, is recognized as an essential trace element for humans and mainly exists in the +4 and +6 valence oxyanions in natural environments and as organic selenium compounds in organisms (Lopes, Avila, & Guilherme, 2017;Zhang, Guan, Yang, Zeng, & Liu, 2018). The antagonistic phenomenon between selenium and mercury has earlier been reported, and numerous studies have shown that selenium supplementation counteracts the negative effects of exposure to mercury (Li, Li, & Feng, 2016;Wang & Wang, 2017;Wang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The concern regarding the quality and capacity of products to supply essential nutrients, including selenium (Se), has increased in recent years. Se contents available in the soil can be absorbed and accumulated in the food for humans and animals (Lopes;Ávila;Guilherme, 2017;Wang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Such action is important to increase Se natural intake by the population, and therefore it is a possible strategy to be used in Brazil. However, to succeed in this practice, studies are required in order to well understand Se sorption behavior in the soils (Lopes;Ávila;, which will assist in the definition of safe doses to be added to fertilizers, since the limit between the essentiality and the toxicity of this element is quite narrow (Sharma et al, 2017).…”
Section: Introductionmentioning
confidence: 99%